The Effect of the Make a Match Type Cooperative Learning Model on Improving Students' Self Efficacy in Social Science Education - Sabrina Bella Fani (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to examine the effect of the make a match cooperative learning model on improving students’ self efficacy in Social Science Education. This research employed a quantitative approach using a quasi experimental design. The population of this study consisted of eighth grade students at SMP Negeri 2 Waru. The sampling technique used was purposive sampling. The sample included two classes: class VIII A as the experimental group and class VIII B as the control group. The data collection techniques in this research used documentation and questionnaires. The research instrument used was a questionnaire. Instrument testing was conducted through validity and reliability tests. Data analysis techniques included normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The results showed that the make a match cooperative learning model had a significant effect on improving students’ self efficacy in Social Science Education. The paired sample t-test indicated a significant difference between the pretest and posttest scores of the experimental class (Sig. 0.009 < 0.05). The independent sample t-test also showed a significant difference in self efficacy between the experimental class and the control class (Sig. 0.000 < 0.05). This indicates that H0 was rejected and Ha was accepted. Therefore, it can be concluded that the make a match cooperative learning model has a significant effect on improving students’ self efficacy in Social Science Education.